Evolution Of Tokaili Settlement Process In Central Sulawesi, Indonesia - Siradjuddin, Zaenal (Advances in Social Sciences Research Journal, 2021)
Indonesia has a variety of (ethnic) cultures spread throughout Indonesia, one of which is in Central Sulawesi (ToKaili). The evolutionary process that is the object of observation is in the ToKaili community, which focuses on seTeori sosiologis klasik menjadikan sosiologis sebagai teori dasar. Di antara hipotesis yang muncul berkaitan dengan idealisme, materialisme dan sistem ekonomi, nilai lebih, dan dinamika perubahan sosial mempengaruhi teori perubahan sosial dari bentuk-bentuk rasionalisme yang dimiliki. Kelompok-kelompok yang dibentuk berdasarkan kepentingan tertentu, menunjukkan konfigurasi kelas (berbasis ekonomi), status (berdasarkan kondisi dan kepentingan sosial), partai (berdasarkan kepentingan politik). Dalam berpikir, rasionalitas, terdapat empat pandangan berbeda tentang model yang ada di antara orang-orang. Di antara keberadaan rasionalitas yang dapat menderita sendirian tetapi juga dapat menjadi rujukan bagi perilaku orang dalam kehidupan mereka (Doyle Paul Johnson, 1986) 9ttlement development. The evolution method does not just happen but has a long process to achieve the ideal form of housing and housing. This study aims to uncover what is behind the phenomenon of home / personal life in ToKaili from traditional architecture. his research uses a qualitative method with a phenomenological approach. This analysis found several development periods ranging from nomadic settlements to permanent settlements, and its development at that time the solution became an ideal settlement.